Owncrypt: um aplicativo web de criptografia de dados no cliente pra o owncloud - NUNES, Bruna Jully Neves (2020)
Currently most storage clouds encrypt the data before it is stored. However, because these clouds also keep the cryptographic keys used in the encryption process, they can easily access the stored content. In order to mitigate this problem, this paper presents OwnCrypt. An application for the OwnCloud frontend that allows the encryption of data on the user's computer before sending to the cloud.